Analysis of interactions between domains of a small heat shock protein, Hsp30 of Neurospora crassa - Plesofsky, Nora (Cell Stress Society International, 2002)
The α-crystallin–related, small heat shock proteins (sHsps), despite their overall variability in sequence, have discrete regions of conserved sequence that are involved in structural organization, as well as nonconserved regions that may perform similar roles in each protein. Recent X-ray diffraction analyses of an archeal and a plant sHsp have revealed both similarities and differences in how they are organized, suggesting that there is variability, particularly in the oligomeric organization of sHsps. As an adjunct to crystallographic analysis of sHsp structure, we employed the yeast 2-hybrid system to detect interactions between peptide regions of the sHsp of Neurospora crassa, Hsp30. We found that the conserved α-crystallin domain can be divided into N-terminal and C-terminal subdomains that interact strongly with one another. This interaction likely represents the tertiary contacts of the monomer that were visualized in the crystallographic structures of MjHsp16.5 and wheat Hsp16.9. The conserved sHsp monomeric fold is apparently determined by these regions of conserved sequence. We found that the C-terminal portion of the α-crystallin domain also interacts with itself in 2-hybrid assays; however, this interaction requires peptide extension into the semiconserved carboxyl tail. This C-terminal association may represent a principal contact site between dimers that contributes to higher-order assembly, as seen for the crystallized sHsps.